Low-velocity impact on square sandwich plates with fibre-metal laminate face-sheets: analytical and numerical research - Zhang, Jianxun (2022)
The low-velocity impact via a heavy mass on clamped square sandwich plates (SSP) composed of metal foam core and fibre-metal laminate (FML) face-sheets is studied by analytical and numerical methods. Low-velocity impact (LVI) is formulated on square FML sandwich plates based on modified rigid-plastic material approximation (RPMA). Numerical simulations are conducted, and then compared with analytical results reasonably. Influences of the material parameters and impact location on the dynamic behaviors are discussed in detail. This work provides an efficient and simply analytical method to predict low-velocity impact for square FML sandwich plates.